Oxidative stress, link between basic sciences and clinical practice - Crespo Retes, Isaac (2015)
Cardiovascular complications, characterized by endothelial dysfunction and accelerated atherosclerosis, are the leading cause of diabetes-associated morbidity and mortality. There is growing evidence that excess generation of highly reactive free radicals, largely due to hyperglycemia, causes oxidative stress, which further exacerbates the development and progression of diabetes and its complications. Overproduction and/or insufficient removal of these free radicals result in vascular dysfunction and damage to cellular proteins, membrane lipids and nucleic acids. Despite overwhelming evidence on the damaging consequences of oxidative stress and its role in experimental diabetes, large scale clinical trials with classic antioxidants failed to demonstrate any benefit for diabetic patients. As our understanding of the mechanisms of free radical generation evolves, it is becoming clear that rather than merely scavenging reactive radicals, a more comprehensive approach aimed at preventing the generation of these reactive species as well as scavenging may prove more beneficial. Therefore, new strategies with classic as well as new antioxidants should be implemented in the treatment of diabetes.